2017
DOI: 10.2147/ndt.s135623
|View full text |Cite
|
Sign up to set email alerts
|

Rapid infusion of esketamine for unipolar and bipolar depression: a retrospective chart review

Abstract: BackgroundThis study evaluated efficacy and safety of intravenous subanesthetic doses of esketamine using an administration time of 10 minutes in patients with treatment-resistant depression and bipolar depression.MethodsA retrospective chart review was conducted to identify patients who met the inclusion criteria for treatment-resistant depression and bipolar depression according to Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision criteria, and these patients received rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 27 publications
0
35
1
1
Order By: Relevance
“…Some researchers showed that the presence of dissociative symptoms is a marker of antidepressant effectiveness [3]. The BPRS and BPRS+ scales indicated the absence of psychosis during the time of assessment [4,25]. Table 2.…”
Section: Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers showed that the presence of dissociative symptoms is a marker of antidepressant effectiveness [3]. The BPRS and BPRS+ scales indicated the absence of psychosis during the time of assessment [4,25]. Table 2.…”
Section: Clinical Relevancementioning
confidence: 99%
“…The current psychopharmacological treatment approaches in depression mainly focus on mood stabilizers, second-generation antipsychotics, and monoaminergic interventions, but a significant proportion of patient do not respond to them adequately. Treatment-resistant bipolar depression (TRBD) patients who do not achieve remission are up to 33% of the depressive patients global count [2][3][4]. Delayed onset of the clinical action of the antidepressants, tolerability of the drugs, comorbidities, and low drug efficacy in some patients are the key unmet challenges of contemporary psychiatry [5].…”
Section: Introductionmentioning
confidence: 99%
“…Electroconvulsive therapy (ECT) has greater efficacy and more rapid onset of action than antidepressant medications; however, mean onset is still >2 weeks (9), open-label remission rates occur in only 50-65% of patients (5), and there are numerous significant off-target effects, including cognitive disturbances (10) and effects on the motor system (11), making it difficult to determine which network changes are specific to remission from depression. Ketamine induces brief remission rapidly but only in a third of patients (12,13) and with significant off-target effects (14,15). Incipient investigations of potent 5-HT2a agonists demonstrate high rates of rapid remission (16,17); yet, the off-target effects are profound (18).…”
Section: Introductionmentioning
confidence: 99%
“…Ketamine/sketamine has recently been FDA-approved for treatment-resistant depression; however, ketamine has several limitations. Approximately 11% of patients report the dissociative symptoms as very disturbing 64 , remission rates for ketamine/s-ketamine are lower than the remission rate we observed for SAINT 33,35,65 , very few studies have investigated the antidepressant efficacy of ketamine beyond a single infusion 66,67 and the opioid mechanism of action poses a potential risk 68 . The other available rapid-acting treatment is ECT, for which less than 2% of eligible patients receive due to concerns regarding cognitive side-effects and stigma 69,70 .…”
Section: Discussionmentioning
confidence: 60%